1984
DOI: 10.1111/j.1365-2141.1984.tb02903.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet crossmatch tests using radiolabelled staphylococcal protein A or peroxidase anti-peroxidase in alloimmunized patients

Abstract: Summary. Refractoriness to random‐donor platelets as a result of alloimmunization remains a major problem in long‐term platelet transfusion therapy despite the use of HLA‐matched platelets. We have therefore studied the use of two methods for detection of platelet associated IgG as platelet crossmatch tests for the selection of platelet donors. These methods use radiolabelled staphylococcal protein A (125I‐SPA) and peroxidase anti‐peroxidase (PAP), respectively. One hundred and ten crossmatch tests using 125I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Significantly higher count increments were described for cross‐match–compatible versus cross‐match–incompatible PLTs in alloimmunized, refractory patients, and for cross‐match–compatible versus un–cross‐matched PLTs (all but one in refractory individuals). Higher increments for cross‐match–compatible units versus cross‐match–incompatible or un–cross‐matched PLTs were also found in other studies but significance was not reported. In nonrefractory patients, three of five studies showed that cross‐match–compatible PLTs did not result in significantly higher CCIs or success rates with four of the five assays studied .…”
Section: Resultsmentioning
confidence: 50%
See 4 more Smart Citations
“…Significantly higher count increments were described for cross‐match–compatible versus cross‐match–incompatible PLTs in alloimmunized, refractory patients, and for cross‐match–compatible versus un–cross‐matched PLTs (all but one in refractory individuals). Higher increments for cross‐match–compatible units versus cross‐match–incompatible or un–cross‐matched PLTs were also found in other studies but significance was not reported. In nonrefractory patients, three of five studies showed that cross‐match–compatible PLTs did not result in significantly higher CCIs or success rates with four of the five assays studied .…”
Section: Resultsmentioning
confidence: 50%
“…Of these, 126 were excluded because they did not fulfill eligibility criteria. The full‐text articles of the remaining 20 citations that met inclusion criteria were retrieved . A search of bibliographies identified an additional 11 references for a total of 31 reports.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations